2015
DOI: 10.1590/1415-52732015000500002
|View full text |Cite
|
Sign up to set email alerts
|

Altura do joelho como medida alternativa confiável na avaliação nutricional de idosos

Abstract: ALTURA DO JOELHO E AVALIAÇÃO NUTRICIONAL | 475Rev. Nutr., Campinas, 28(5):475-484, set./out., 2015 Revista de Nutrição R E S U M O ObjetivoAvaliar o uso da altura do joelho como medida alternativa confiável na avaliação nutricional de idosos atendidos em um ambulatório de geriatria. MétodosEstudo transversal com idosos atendidos em ambulatório de geriatria de um hospital universitário, entre novembro de 2009 e novembro de 2010. Variáveis investigadas: gênero, idade, peso, estatura, altura do joelho, estatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
3
1
1
2
Order By: Relevance
“…The results found differ from other studies, such as Closs et al 17 , which showed that knee height may be a reliable alternative measure in the nutritional assessment of older adults. Using sample composed of 186 individuals (74.3 ± 7.1 years), the author found positive correlation between measured height and height estimated by Chumlea's equation, although the predicted result overestimated the actual measurement by 3 cm.…”
Section: Discussioncontrasting
confidence: 99%
“…The results found differ from other studies, such as Closs et al 17 , which showed that knee height may be a reliable alternative measure in the nutritional assessment of older adults. Using sample composed of 186 individuals (74.3 ± 7.1 years), the author found positive correlation between measured height and height estimated by Chumlea's equation, although the predicted result overestimated the actual measurement by 3 cm.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study evaluated elderly attending CRASI/UFF nutrition clinic. The higher proportion of women has already been described in other studies and can be explained by differences in mortality between the sexes, where men tend to die earlier, since women have less exposure to risk factors, such as smoking and alcoholism, and seek more the health services, with a higher life expectancy 17,18 .…”
Section: Discussionsupporting
confidence: 51%
“…Knee height was measured using an Indaiá wooden stadiometer for children, with maximum measurement of 100cm and 0.1cm precision; using the equation suggested by Chumlea 17 (method most recommended for the elderly) to estimate the height of each elderly person. 18 Information on food consumption in the last seven days was obtained by means of an abridged Food Frequency Questionnaire (FFQ), 19 prepared according to recommendations described in the version of the Food Guide for the Brazilian Population in force at the time the study was planned (2013). 20 Questions were asked about consumption of the following food items: rice and beans; wholefoods (wholemeal bread, wholemeal biscuits, wholegrain rice or oats); vegetables and greens; fruit; meat; milk and milk products; confectionary, soft drinks and industrialized fruit juice; fried food; conserves, charcuterie and tinned food; frozen food; and fast food.…”
Section: Methodsmentioning
confidence: 99%